PENYULUHAN KEWIRAUSAHAAN DAN CARA PENANAMAN PEPAYA CALIFORNIA PADA LAHAN KOSONG UNTUK MENINGKATKAN KESEJAHTERAAN BURUH TANI - Purnadi Purnadi; Hengky Widhiandono; Akhmad Darmawan (Media Ekonomi, 2017)
Improving the welfare of farm laborers may do with the counseling program and Pepaya california growing practices. This program provides knowledge about business prospect and how to plant Pepaya california by a farmer who have been successful and experienced. There should be proper coordination of all parties to such social programs can be run properly. Keywords: Welfare, Farm Laborers, Counseling Program, Papaya California.